2022
DOI: 10.1002/pen.26057
|View full text |Cite
|
Sign up to set email alerts
|

Design, preparation, and characterization of silk fibroin/carboxymethyl cellulose wound dressing for skin tissue regeneration applications

Abstract: Silk fibroin (SF) has been broadly applied in wound dressing fabrication because of its proper features for wound healing. In this work, we developed a carboxymethyl cellulose (CMC)/gelatin blend film with different concentrations of glycerol, and modified the optimized film with an SF layer through electrospinning process. Tensile strength and cell viability evaluation of blend films demonstrated that the glycerol content of 3% could be suitable as the substrate layer for the two‐layer wound dressing. The mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…[ 57 ] The incorporation of silk fibroin has improved the mechanical strength properties of the CMC/gelatin blend film and these films indicated the interection of the structure with the skin for better wound care applications. [ 58 ] The literature reports [ 59–64 ] and present research work indicated that the present material (AIG‐cl‐carbopol‐co‐poly(AAm) polymers) formed in the form of hydrogel films can act as potential wund dressing materials.…”
Section: Resultsmentioning
confidence: 71%
“…[ 57 ] The incorporation of silk fibroin has improved the mechanical strength properties of the CMC/gelatin blend film and these films indicated the interection of the structure with the skin for better wound care applications. [ 58 ] The literature reports [ 59–64 ] and present research work indicated that the present material (AIG‐cl‐carbopol‐co‐poly(AAm) polymers) formed in the form of hydrogel films can act as potential wund dressing materials.…”
Section: Resultsmentioning
confidence: 71%
“…In addition, the rate of skin regeneration and angiogenesis in the animal model could be accelerated ( Ragothaman et al., 2021 ). In 2022, Farshi and coworkers have developed blends based on carboxymethyl cellulose and gelatin with different concentrations of glycerol and modified the film using silk fibroin layer using electrospinning technique ( Farshi et al., 2022 ). Various polymer based nanomaterials for skin tissue engineering applications are tabulated in Table 7 .…”
Section: Skin Tissue Engineeringmentioning
confidence: 99%
“…Apart from their significance in regenerative medicine, antimicrobials, drug delivery, and stem biology, Nanobiomaterials can be used for the treatment of diabetes mellitus 1 by generating supplemental oxygen required by islets until the formation of blood vessels ( Gholipourmalekabadi et al, 2016 ). Electrospinning uses the principles of nanobiotechnology for the preparation of biocompatible scaffolds which mimic collagen nanofibers providing protection and mechanical support at the injury site ( Farshi et al, 2022 ).…”
Section: Effects Of Nanoparticles On B Cellsmentioning
confidence: 99%